Relationships between compressive strength of cement-slag mortars under air and water curing regimes - Sajedi, F.; Razak, Hashim Abdul; Mahmud, H.B.; Shafigh, P. (Elsevier, 2012)
In this investigation 12 mortar mixes including three groups were prepared using binder contents 380 and 500 kg/m 3. All the specimens were cured after casting and demoulding in curing regimes, i.e. at room temperature (ac) and in water (wc). The highest strength was obtained for cement-slag mortars 380-wc at later ages as 80 MPa. For all groups of mortars, there could rarely be strength loss at later ages. It was observed that in duration of 3-7 days, wc is the optimum for all groups of mortars with exception of cement mortar 500 and slag mortar 500. In duration of 28-90 days, wc is also the optimum for three groups of mortars with exception of cement mortar 500. It was revealed that an exponential relationship exists between the strengths obtained in air and water curing conditions for each group of mortar, i.e. with and without using ground granulated blast furnace slag. It was proved that higher strengths could be obtained using lower binders' contents for cement and cement-slag mortars provided the specimens were cured in water. This is a new finding having importance from economic and environmental viewpoints; meaning that for producing higher strengths it is not a necessity to use more binders. It was found that increase in level of cement and slag makes the mortars more sensitive to air curing conditions. Â© 2012 Elsevier Ltd. All rights reserved.